Building a Web and Mobile-Based Academic Information System for Optimizing Pesantren Management (Case Study: Pondok Pesantren Nurussalam Krapyak) - Khairul Aqila, Muh Agna; Sutarrman , Sutarrman (Jurnal Indonesia Sosial Sains, 2025)
This research aims to develop a web-based and mobile-based Islamic boarding school academic information system to improve the efficiency of academic data management. This system integrates a web dashboard for admins and a mobile application for students through an Application Programming Interface (API). The development method used is the Waterfall model which includes the stages of needs analysis, system design, implementation, and testing. The test is carried out using the Black Box Testing method to ensure the functionality of the system runs properly. The results of the study show that the developed system is able to manage academic data, attendance, schedules, and announcements effectively and supports the process of digitizing the academic administration of Islamic boarding schools.